2019
DOI: 10.1134/s1063776119040010
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological Extension for Tidal Charge Black Hole

Abstract: A simple phenomenological extension of the black hole solution with tidal charge is proposed. Empirical data on the Sgr A* is consistent with the suggested metric which serves as a generalisation of the Reissner-Nordström one. Such a generalisation includes the leading effects beyond general relativity so, the discussed metric can explain wider range of gravitational effects. We discuss physical features of an object described by the proposed metric, namely, the size of its shadow and the innermost stable circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…5). As we demonstrated earlier [19] in minimally extended BH model the shadow sizes less than 4R Sw appear. Such BH does not exist in Kerr-Newman model and could be the indication of extended gravity appearance.…”
Section: Shadow Analyzesupporting
confidence: 76%
See 2 more Smart Citations
“…5). As we demonstrated earlier [19] in minimally extended BH model the shadow sizes less than 4R Sw appear. Such BH does not exist in Kerr-Newman model and could be the indication of extended gravity appearance.…”
Section: Shadow Analyzesupporting
confidence: 76%
“…In the vanishing inclination (θ i = 0) case the shadow becomes circularly symmetrical (like in the non-rotating case) but slightly compressed due to the rotation. Previously [19] we demonstrated that two non-rotating BHs with different parameters could have the same shadow size. In the rotating case each point of the shadow edge can be treated as the image of the BH's potential since it corresponds to the unique photon orbit radius r 0 .…”
Section: Shadow Analyzementioning
confidence: 97%
See 1 more Smart Citation
“…( 26) in [62]. We also refer to Alexeyev et al [63] for possible generalizations. With known b cr , the angular radius α sh of the shadow can now be found for an arbitrary position of the observer using eq.…”
Section: Example 1: Shadow In Schwarzschild Space-timementioning
confidence: 97%
“…Since for solar and bigger than solar masses of the black hole the solution does not differ from Schwarzschild, no observable effects can make the solution distinguishable, although in the microphysics the difference could be detectable [46]. Additional constraints on the "tidal charge" could be placed by considering circular orbits and the black hole shadows [48,49].…”
Section: Black Hole With the Tidal Chargementioning
confidence: 99%